Isolation and identification of a viral haemorrhagic septicaemia virus (VHSV) isolate from wild largemouth bass Micropterus salmoides in China. Issue 11 (23rd August 2019) - Zhang, Wanwan; Li, Zelin; Xiang, Yangxi; Jia, Peng; Liu, Wei; Yi, Meisheng; Jia, Kuntong
Abstract: Fish rhabdoviruses are a family of viruses responsible for large‐scale fish die‐offs worldwide. Here, we reported the isolation and identification of a member of rhabdoviruses from wild largemouth bass ( Micropterus salmoides ) in the coastal area of the Pearl River Estuary, China. This virus isolate was identified as viral haemorrhagic septicaemia virus (VHSV) by specific RT‐PCR. Furthermore, the virus (VHSVLB2018) was isolated by cell culture using fathead minnow cells and confirmed by RT‐PCR. Electron microscopy showed the presence of bullet‐shaped viral particles in the cytoplasm of infected cells. The complete sequencing of VHSVLB2018 confirmed that it was genome configuration typical of rhabdoviruses. Phylogenetic analysis based on whole‐genome sequences and G gene nucleotides sequences revealed that VHSVLB2018 was assigned to VHSV genogroup Ⅳa. The pathogenicity of VHSVLB2018 was determined in infection experiments using specific pathogen‐free largemouth bass juveniles. VHSVLB2018‐infected fish showed typical clinical signs of VHSV disease, including darkened skin, petechial haemorrhages and pale enlarged livers, with the cumulative mortalities reached 63.3%–93.3% by 7 days post‐infection. VHSVLB2018 was re‐isolated from dead fish and confirmed by RT‐PCR. Together, this is the first report of isolation and identification of a VHSV isolate from wild largemouth bass in China.